2017
DOI: 10.1155/2017/3782687
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Multifactor Modelling of Weighted-Mean Temperature for Ground-Based GNSS Meteorology in Hunan, China

Abstract: In this study, radiosonde observations during the period of 2012-2013 from three stations in the Hunan region, China, were used to establish regional Tm models (RTMs) that are a fitting function of multiple meteorological factors (Ts, Es, and Ps). One-factor, two-factor, and three-factor RTMs were assessed by comparing their Tm against the radiosonde-derived Tm (as the truth) during the period of 2013-2014. Statistical results showed that the bias and RMS of the one-factor RTM, in comparison to the BTM result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…where Π is the conversion coefficient to be estimated, and the ρ w , R v , k 2 and k 3 are all constants which can be found in the literature studies [6,15,[21][22][23]. However, the weighted mean temperature (T m ) is a variable that determines the final value of Π, thus plays a decisive role in the GNSS-PWV retrieval.…”
Section: The Determination Of T M 21 Computing T M By Numerical Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…where Π is the conversion coefficient to be estimated, and the ρ w , R v , k 2 and k 3 are all constants which can be found in the literature studies [6,15,[21][22][23]. However, the weighted mean temperature (T m ) is a variable that determines the final value of Π, thus plays a decisive role in the GNSS-PWV retrieval.…”
Section: The Determination Of T M 21 Computing T M By Numerical Integrationmentioning
confidence: 99%
“…The Bevis formula (T m = a • T s + b) was first used to calculate T m [6], its coefficients were fitted from the radiosonde data distributed in the North America, but it was found that the relation between T m and T s varies with the locations and seasons, so a Bevis formula with constant coefficients a and b would result in poor accuracy when estimating T m in different locations and seasons. Many scholars have conducted the localization research on the Bevis formula and found that the model coefficients tailored to the specific locations and seasons can better fit the local conditions [15,[23][24][25][26]. Some MMTm models for global GNSS-PWV retrieval have also been developed, such as the GTm-I model, PTm-I model [8] and the TVGG model [27].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracies of the other two models were both better than that of the currently used Hong Kong regional models, with the RMSs of 1.91 K and 1.89 K [49]. However, some studies have shown that the accuracies of T m in different seasons are different because the sun radiates differently to the ground in different seasons [47], [50], [51]. Thus, to further improve the accuracy of T m models developed based on RS data from one year or more, four new seasonal models were developed based on RS data from each season during the period 2014 -2016.…”
Section: B Accuracy Of T Mmentioning
confidence: 99%
“…According to the data of 8718 radiosonde stations in the United States (27~60 • N), Bevis et al [5] obtained the unary linear expression of Tm and the surface temperature (Ts): Tm = 0.72Ts + 70.2. This modeling method is simple and practical, and high precision can be obtained in certain areas, so some experts have improved it and established corresponding localized models for different areas [6][7][8]. However, the precision 2 of 13 of this type of model is limited by the scope of the study area, and ensuring that highprecision Tm estimates can be obtained in other areas is difficult.…”
Section: Introductionmentioning
confidence: 99%